2010
DOI: 10.1016/j.gca.2010.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Temperature induced decoupling of enzymatic hydrolysis and carbon remineralization in long-term incubations of Arctic and temperate sediments

Abstract: Extracellular enzymatic hydrolysis of high-molecular weight organic matter is the initial step in sedimentary organic carbon degradation and is often regarded as the rate-limiting step. Temperature effects on enzyme activities may therefore exert an indirect control on carbon mineralization. We explored the temperature sensitivity of enzymatic hydrolysis and its connection to subsequent steps in anoxic organic carbon degradation in long-term incubations of sediments from the Arctic and the North Sea. These sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 46 publications
(58 reference statements)
4
32
0
Order By: Relevance
“…Surface sediment collected in March 2011 was centrifuged as described above Recalcitrant DOC contributes to net accumulation of DOC in sediment pore waters. Dashed arrows indicate two possible pathways of recalcitrant DOC production: (a) internal conversion of labile DOC (pore-water size reactivity model; Burdige and Gardner 1998); (b) direct production from POC through hydrolysis (Weston and Joye 2005;Robador et al 2010). Methanogenesis has been excluded for simplicity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface sediment collected in March 2011 was centrifuged as described above Recalcitrant DOC contributes to net accumulation of DOC in sediment pore waters. Dashed arrows indicate two possible pathways of recalcitrant DOC production: (a) internal conversion of labile DOC (pore-water size reactivity model; Burdige and Gardner 1998); (b) direct production from POC through hydrolysis (Weston and Joye 2005;Robador et al 2010). Methanogenesis has been excluded for simplicity.…”
Section: Methodsmentioning
confidence: 99%
“…1). More recently, Robador et al (2010) proposed another model where DOC accumulates because of inherent recalcitrance of DOC that is produced during POC hydrolysis (Weston and Joye 2005;Fig. 1).…”
mentioning
confidence: 99%
“…The response of aquatic ecosystems to warming temperatures is complicated, but is expected to greatly affect the rates and mechanisms for OM production and decomposition (Canuel et al, 2012). Some studies suggest that metabolism may be more impacted by varying temperatures compared to primary production under warming temperatures (López-Urrutia et al, 2006), which could result in lower biomass yields throughout trophic levels along with altered microbial metabolic pathways and trophic linkages (Weston and Joye, 2005;Robador et al, 2010), particularly in waters affected by eutrophication (O'Connor et al, 2009). Alterations to the delivery, storage, processing, and transport of material through estuaries due to perturbations such as land use change and increased urbanization in watersheds are recorded in marine sediment records.…”
Section: Estuarine Om Transport Burial and Transformationmentioning
confidence: 99%
“…Studies of temperature responses of microbial processes in marine sediments have shown that rates of both hydrolysis and fermentation exceed the terminal mineralization at higher temperatures compared to normal conditions (Weston & Joye 2005, Robador et al 2010. As a result, dissolved OM (DOM) may accumulate in the pore waters at higher temperatures, as the sulfate-reducing bacteria are not able to keep up with the production (Robador et al 2010). In our experiment, however, we neither observed detectable changes in the DOC pools during the duration of the experiment, nor did we observe that DOC accumulation was affected by temperature.…”
Section: Mineralization Rates In Mat Materialsmentioning
confidence: 99%
“…Assuming a bacterial C:N ratio of about 5 (Gold man et al 1987, Fagerbakke et al 1996) and a C:N ratio for plant detritus > 25, all NH 4 + from hydrolysis and fermentation can potentially be re-assimilated by bacteria (Blackburn 1979). Mineralization of OM may be limited in any of the steps in the decay pathway (Arnosti et al 1998, Robador et al 2010, and temperature is one factor that affects the bacterial activity. Bacteria typically respond to temperature with a Q 10 of about 2 to 3 up to the optimum temperature for growth (Pomeroy & Wiebe 2001).…”
Section: Introductionmentioning
confidence: 99%